Hubungan Asupan Vitamin E dan Vitamin C dengan Kadar Kolesterol Total pada Pasien Hiperkolesterolemia - Amilia Yuni Damayanti; Akfina Rizki Anjana; Joyeti Darni (Universitas Islam Negeri Walisongo Semarang, 2020)
AbstractThis study aims to determine the correlation between vitamin E and vitamin C intake with total cholesterol levels in the hypercholesterolemic patient. The research design was cross-sectional type with 30 samples whose diagnosed with hypercholesterolemia in January 2019 at Tlogosari Kulon Health Center, Semarang. The intake of vitamin E and vitamin C was obtained using a semi-quantitative food frequency questionnaire (SQFFQ). Total cholesterol data were collected from the result of the patient’s blood test with cholesterol levels above 200 mg/dl. The analysis used was univariate and bivariate analysis to determine the correlation between the intake of vitamin E and vitamin C with total cholesterol levels. The bivariate analysis used the Spearman Rank. The average intake of vitamin C and E of respondents is classified as less, namely 34.51 mg and 0.12 mg in a day. There was no significant correlation between vitamin E intake and total cholesterol levels (p-value =0.13 ), there was no significant correlation between vitamin C intake and total cholesterol levels (p-value =0.39). Vitamin E and vitamin C intake are not related to total cholesterol levels in hypercholesterolemic patients. AbstrakPenelitian ini bertujuan untuk mengetahui hubungan antara asupan vitamin E dan vitamin C dengan kadar kolesterol total pada pasien yang mengalami Hiperkolesterolemia. Desain penelitian adalah cross sectional dengan (n=30) yang baru didiagnosa Hiperkolesterol pada bulan Januari 2019 di Puskesmas Tlogosari Kulon Semarang. Asupan vitamin E dan vitamin C diperoleh dengan menggunakan semi quantitative food frequency questionnaire (SQFFQ). Data kolesterol total diperoleh dari hasil tes laboratorium kimia darah pasien dengan kadar kolesterol di atas 200 mg/dl. Analisis yang digunakan adalah analisis univariat dan bivariat untuk mengetahui hubungan antara asupan vitamin E dan vitamin C dengan kadar kolesterol total. Analisis univariat yang digunakan adalah uji normalitas dan bivariat adalah uji Spearman Rank. Rata-rata asupan vitamin C dan E responden tergolong kurang, yaitu 34,51 mg dan 0,12 mg per hari. Tidak ada hubungann signifikan antara asupan vitamin E dengan kadar kolesterol total (p-value =0,13 ), tidak ada hubungan signifikan antara asupan vitamin C dengan kadar kolesterol total (p-value =0,39). Asupan vitamin E dan vitamin C tidak berhubungan dengan kadar kolesterol total pada pasien Hiperkolesterolemia.